Sociology of education in India : changing contours and emerging concerns - Nambissan, Geetha B., 1955-; Srinivasa Rao. (New Delhi : Oxford University Press, 2013)
This text traces the trajectory, location, and concerns of the discipline of sociology of education in India. It makes theoretical and empirical engagements with the emerging key concerns of education today, which include themes of equality identity, cultural diversity, and exclusion.
Includes bibliographical references.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Educational sociology -- India